2021
DOI: 10.1155/2021/5585239
|View full text |Cite
|
Sign up to set email alerts
|

TaiChi and Qigong for Depressive Symptoms in Patients with Chronic Heart Failure: A Systematic Review with Meta-Analysis

Abstract: Background. Depression is a debilitating comorbidity of heart failure (HF) that needs assessment and management. Along with mind-body exercise to deal with HF with depression, the use of TaiChi and/or Qigong practices (TQPs) has increased. Therefore, this systematic review assesses the effects of TQPs on depression among patients with HF. Methods. Randomized controlled trials (RCTs) that examined the effect of TQPs on depression in patients with HF were searched by five databases (PubMed, Cochrane Central Regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 45 publications
(127 reference statements)
2
5
0
Order By: Relevance
“…The NMA results supported that Tai chi can significantly alleviate depressive symptoms among BC patients, which was consistent with other meta‐analyses (Jiang et al, 2021; Qi et al, 2022; Wang et al, 2014). The rank probability of the efficacy suggested that Tai chi (SUCRA = 76.9%) demonstrated the most comparable effects to Liuzijue (SUCRA = 95.4%) among the other MBE interventions for improving depression.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The NMA results supported that Tai chi can significantly alleviate depressive symptoms among BC patients, which was consistent with other meta‐analyses (Jiang et al, 2021; Qi et al, 2022; Wang et al, 2014). The rank probability of the efficacy suggested that Tai chi (SUCRA = 76.9%) demonstrated the most comparable effects to Liuzijue (SUCRA = 95.4%) among the other MBE interventions for improving depression.…”
Section: Discussionsupporting
confidence: 90%
“…are not yet clear. The scarcity of high-quality research, as well as limitations such as short follow-up periods, restrict its application The NMA results supported that Tai chi can significantly alleviate depressive symptoms among BC patients, which was consistent with other meta-analyses (Jiang et al, 2021;Qi et al, 2022;Wang et al, 2014). The rank probability of the efficacy suggested that Tai Qi and removing blockages that can lead to poor health according to traditional Chinese medicine (Yeung et al, 2018).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…With the increasing global popularity of TCE, it is more widely utilized in cardiac rehabilitation (CR) programs for HF patients. Reported benefits of TCE include improvements in clinical symptoms, QoL, exercise tolerance, cardiac function, sleep quality, and the alleviation of depressive symptoms in patients with HF [ 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. Several randomized controlled trials (RCTs) reported that left ventricular ejection fraction (LVEF) and N-terminal pro-B natriuretic peptide (NT-proBNP) had no noticeable improvement within 3 months of Liuzijue exercise [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies suggest that Taijiquan and Qigong have several mental health benefits [ 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. These techniques are suggested to assist in managing anxiety and depression in children and adolescents [ 18 , 24 ] as well as in patients with several health conditions such as breast cancer in women [ 20 ] or heart failure in elders [ 21 ], for example. The dimension of benefits seems to also reach other complex conditions such as autism [ 22 ] or ADHD [ 23 ].…”
Section: Introductionmentioning
confidence: 99%